Autopsy Report with Clinical and Pathophysiologic Discussion of Autosomal Dominant Adult Polycystic Kidney Disease. (17th September 2014) - Hazra, Anup; Siderits, Richard; Rimmer, Cheryl; Rolleri, Noah
Abstract : The average weight of a kidney is approximately 135 gm, measuring on average 10 × 6 × 4 cm. In hereditary conditions, autosomal dominant and autosomal recessive polycystic kidney disease, the shape, size, and the weight can be significantly abnormal, causing progressive renal failure, often necessitating dialysis or renal transplant for survival. We report a case of adult polycystic kidney disease in a 50-year-old female without a family history, who died of complications of the disease which included accelerated hypertension, and renal and cardiac failure.